Understanding database management system - Mattison, Rob (McGraw-Hill series on data warehousing and data management., 1998)
This practical guide offers a detailed examination of database architectures, including relational, pre-relational, distributed and object-oriented designs. It discusses the fine points of each architecture. and explores the specific configurations of current database products offered on UNIX, mainframe, and PC platforms. It also covers all the latest technology: OLAP, ROLAP and SMP/NUMA. The book outlines a methodology for the systematic appraisal of database products using a commonly definable set of profiles covering: architecture, programming issues, data storage techniques, administration utilities and distributed capabilities. Using this approach, readers should have a complete set of benchmarks for choosing the optimum system to meet their unique needs. Rob Mattison is the author of "Data Warehousing".